Implementation of Reading, Questioning and Answering (RQA) Learning Strategies in Improving Learning Outcomes of Class XI Students of SMA 6 Kerinci - Nesi Fania; M Eval Setiawan; Eka Putra (Journal of Biological Science and Education, 2021)
The RQA (reading, questioning, and answering) learning model is an active learning model that emphasizes reading, asking, and answering. This study aims to determine the application of reading, questioning, and answering (RQA) learning strategies in improving student learning outcomes in class XI SMA N 6 Kerinci. This research is a type of quantitative research with experimental methods. The research population came from class XI SMA N 6 Kerinci, amounting to 44 people. The sample came from class XI MIPA 2, which amounted to 22 people. The sampling technique in this research is the random sampling technique. Data collection techniques in the form of observation and tests. The test is used to see student learning outcomes using reading, questioning, and answering (RQA) learning strategies. The research instrument is a test in the form of objective questions totalling 30 items carried out for validity, reliability, difficulty index and discriminatory power. Data analysis technique using T-test and N-Gain. The results showed that 1) the results of the study before applying the RQA strategy the highest score of students was 70 and the lowest score was 40 with an average pretest score of 51.59, 2) student learning outcomes after implementing the RQA learning strategy obtained the highest score of 90 and the lowest score of 65 with the result the average posttest is 78.18, 3) there is a significant difference in the application of the RQA strategy in improving student learning outcomes in class XI SMA N 6 Kerinci. Keywords:   Strategy of RQA, Learning Outcomes,